The Role of Nasyiatul Aisyiah in Realizing Women Equality according to the Principles of Progressive Islam - Adrian Ali; Helmiati Helmiati (Program Pascasarjana IAIN Langsa, 2026)
The social and economic disparities faced by women in Muslim societies indicate that efforts to achieve gender equality still face significant challenges, including the limited availability of empowerment models based on progressive religious values. This study aims to analyze the role of Nasyiatul Aisyiyah in promoting gender equality based on the principles of Progressive Islam. The study employs a qualitative approach using literature review and document analysis methods, drawing from academic literature, organizational documents, and relevant prior research. Data were analyzed thematically to identify the relationship between the concept of Progressive Islam and women’s empowerment practices. The findings reveal that Nasyiatul Aisyiyah’s women’s empowerment initiatives are not merely programmatic interventions but represent a practical translation of Progressive Islam values into community-based empowerment strategies. Through entrepreneurship training, leadership development, and capacity-building programs, the organization promotes women’s agency, self-reliance, and active participation in public life. These initiatives reflect the Progressive Islamic principles of social justice, gender equality, and human empowerment by creating opportunities for women to strengthen their economic independence while simultaneously enhancing their role in decision-making processes within families and communities. This empowerment model demonstrates that Progressive Islam functions not only as a normative framework but also as an operational strategy that integrates religious values with efforts to transform gender relations and expand women’s social participation. These findings affirm that the integration of Progressive Islam values with contextual and participatory empowerment strategies constitutes an effective model for advancing women’s equality within Muslim societies. Furthermore, the study contributes to reinforcing a paradigm of women’s empowerment grounded in progressive Islamic values, while also offering a conceptual contribution to the development of Progressive Islam studies regarding gender equality issues.